Despite Crises and Turmoil – High Time for Change: Thoughts on the Global Ecumenical Theological Institute and the 11th Assembly of the World Council of Churches. Issue 3 (26th September 2022) - Weber, Max
Abstract: In August–September 2022, the WCC will gather in Karlsruhe, Germany, for its 11th Assembly around the theme "Christ's love moves the world to reconciliation and unity." In conjunction with the assembly, the Global Ecumenical Theological Institute (GETI) will bring together about 100 participants aged between 21 and 39 years to explore the theme "Christ's love (re)moves borders." Against the background of the GETI theme, this article explores some of the most pressing local and global issues. Based on these impressions, the author sets out his personal hopes and expectations for the GETI study programme and the WCC assembly in Karlsruhe.